Предмет: Алгебра,
автор: марина87
помогите упростить выражение (125x^-6)-^23
Ответы
Автор ответа:
0
(125*x^-6)/^-2/3=125^-2/3 * x^(-6)*(-2/3)= 5^-2 * x^4= 0,04*x^4
Автор ответа:
0
(125x^-6)-^23=125^(-2/3)*(x^(-6))^(-2/3)=
=(корень кубический из 125)^(-2) * x^((-6)*(-2/3))=5^(-2) * x^(-6*(-2):3)=
=(1:(5^2)) * x^(12:3)=(1:25) * x^4=0,04*x^4
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Окружающий мир,
автор: zanadilovruslan7
Предмет: Информатика,
автор: Dizell9005
Предмет: Геометрия,
автор: uratorres